Biomarkers for drug discovery : important aspects of in vitro assay design for HTS and HCS bioassays - Irwin, William A.; Jelić, Dubravko, inženjer kemije; Antolović, Roberto (2008)
Summary: It is generally accepted that insects primarily synthesise oligomannosidic and paucimannosidic N-glycan structures. Indeed, insects' capability to produce human-like complex type N-glycans has been a matter of controversy for a number of years. The relative or complete lack of these structures was primarily attributed to low (or undetectable) activities of the glycosyltransferases needed to drive the synthesis of hybrid and complex type N-glycans (i.e., b-1,2-N-acetylglucosaminyltransferases I and II, b-1,4-galactosyltransferase, a-2,3- and a-2,6-sialyltransferases). Recent developments, fuelled by availability of genomic sequences and by advances in relevant methodologies, have shed some light on the subject, with a few unexpected twists. The identification of a transmembrane/Golgi hexosaminidase, an enzyme which removes a non-reducing N-acetylglucosamine residue during N-glycan biosynthesis, has demonstrated that the synthesis of complex-type N-glycans is actively and deliberately being prevented in insects. On the other hand, the characterisation of an active a-2,6-sialyltransferase in Drosophila, combined with the occurrence of sialylated N-glycan structures as detected in a detailed analysis of Drosophila embryos, has clearly shown that insects can, and need to, synthesise low levels of these structures. The current understanding of the insect N-glycan biosynthetic pathways taking place in Golgi apparatus and trans-Golgi network are elaborated and discussed
Bibliografija: 16 jed
Sažetak
Keywords: Tehnologija visokoproduktivnog probira -- Tehnologija visokosadržajnog probira -- Istraživanje novih lijekova -- Stanični testovi